RELACIONES QUE ESTABLECEN LAS MUJERES DURANTE EL EMBARAZO, PARTO Y POSPARTO CON EL PERSONAL DE SALUD SEGÚN CLASE SOCIAL EN BOGOTÁ: ESTUDIO CUALITATIVO. - Bedoya-Ruiz, Libia A.; Agudelo-Suárez, Andrés A.; Restrepo-Ochoa, Diego A. (Revista Peruana de Medicina Experimental y Salud Pública, 2020)
Objective: To understand the relationship established between women in a situation of pregnancy, childbirth and postpartum with the health services personnel according to social class in Bogotá (Colombia). Materials and methods: Qualitative study. Critical hermeneutical perspective and critical ethnography. Theoretical sampling. Analysis by triangulation in Atlas.ti. 9 women and 8 health professionals participated. 38 in-depth interviews were conducted for 13 months and 62 accompaniments to the maternal in the activities of prenatal control, vaccination, labor, postpartum consultation, follow-up exams, prophylactic pisco course, hospitalization and waiting room, both in public services as private. Results: There are inequalities according to social class in which the relationship between women and staff is configured in the following aspects: permeability to the needs of women, recognition of psychosocial aspects, having different points of view against a medical recommendation and right to complain or demand to improve. Conclusions: The situation described above intensifies gender issues in women with a less advantageous social class. It is necessary to develop interventions in educational and health institutions that consider aspects where human resources are sensitized on social issues related to the theoretical proposals of research and the democratization of medical information. It is unfair that the condition of social class and gender affects the quality of care and economically stratifies people's rights.